Regional political elite: principles of structures and lobbying of interests - Ворчакова, І. Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The actual problem of the formation and development of regional political elite in Ukraine. Drawing an analogy operation of the respective political elites in Russia and Ukraine . The dependence of the development of regional lobbying from level structuring and hierarchization of regional elites. It is proved that a necessary condition for the development of regional policyprocess is the formation of a strong regional team, which could represent, protect and fulfill the interests of all nations  level.